PERAN DINAS SOSIAL DALAM MENYALURKAN BANTUAN SEMBAKO PADA MASA PANDEMI COVID-19 DI KOTA MAKASSAR (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
This study raised the subject matter of "The Role of the Social Service in Distributing Basic Food Aid during the Covid-19 Pandemic in Makassar City", with sub-problems namely: 1) What are the steps of the Social Service in distributing basic food assistance in Makassar City and 2) What are the obstacles What are the problems faced by the Social Service in distributing basic food assistance in Makassar City? This research is qualitative research that discusses the role of the Social Service in Distributing Basic Food Aid during the Covid-19 Pandemic in Makassar City which is located at the Makassar City Social Service office using a research approach that is a scientific discipline that is used as a reference in analyzing the object under study in accordance with logic. that science. The primary data sources in this study were the Head of the Social Extension Section as the main informant, the Problem Handling Counselor at the Social Service Office, and the Head of the Social Extension Section at the Makassar City Office, and the community receiving basic necessities as additional informants. Secondary data sources in this study are books, journals, the internet, and other data sources as complementary data. This type of research is descriptive qualitative research. Data were collected by conducting observations, interviews, documentation, and reference searches. Data processing techniques go through three stages, namely: observation, data presentation, and drawing conclusions. The results of the study show that 1) The role of the Social Service in terms of policies, regulations, and strategies for distributing social assistance in the form of basic necessities in Makassar City has been carried out well. This can be seen from the target of distributing basic necessities by the Social Service, with the updating of data on social assistance recipients in coordination with the relevant institutions. 2) Obstacles faced by the Social Service are lack of time in distributing basic necessities, community data errors, and community turmoil that is too high.